2018
DOI: 10.1021/acsami.7b18596
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline Diamond Coating of Additively Manufactured Titanium for Biomedical Applications

Abstract: Additive manufacturing using selective laser melted titanium (SLM-Ti) is used to create bespoke items across many diverse fields such as medicine, defense, and aerospace. Despite great progress in orthopedic implant applications, such as for "just in time" implants, significant challenges remain with regards to material osseointegration and the susceptibility to bacterial colonization on the implant. Here, we show that polycrystalline diamond coatings on these titanium samples can enhance biological scaffold i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 55 publications
6
76
0
Order By: Relevance
“…Carbon coatings (in the form nanocrystalline or polycrystalline diamond, diamond-like carbon, amorphous carbon, carbon nanotubes, graphene) have non-cytotoxic character and are often used in the engineering of biomaterials to coat metallic biomaterials ( Figure 3), providing them better biocompatibility, what has been reported by many findings [28,[54][55][56][57]. For example, Zhang et al [54] revealed that amorphous carbon-coated β-TCP enhanced adhesion and proliferation of rat BMDSCs.…”
Section: Inorganic and Composite Coatingsmentioning
confidence: 92%
See 1 more Smart Citation
“…Carbon coatings (in the form nanocrystalline or polycrystalline diamond, diamond-like carbon, amorphous carbon, carbon nanotubes, graphene) have non-cytotoxic character and are often used in the engineering of biomaterials to coat metallic biomaterials ( Figure 3), providing them better biocompatibility, what has been reported by many findings [28,[54][55][56][57]. For example, Zhang et al [54] revealed that amorphous carbon-coated β-TCP enhanced adhesion and proliferation of rat BMDSCs.…”
Section: Inorganic and Composite Coatingsmentioning
confidence: 92%
“…Moreover, in vivo experiments showed that amorphous carbon coating enhanced the early bone regeneration capacity. Rifai et al [55] showed that polycrystalline diamond coating on Ti scaffold promoted attachment and proliferation of Chinese Hamster Ovarian (CHO) cells and enhanced apatite deposition. In turn, Tien et al [56] demonstrated that ultra-nanocrystalline diamond coating on silicon microchip reduced foreign-body response and protected the biomaterial from degradation in vivo.…”
Section: Inorganic and Composite Coatingsmentioning
confidence: 99%
“…Meanwhile, using polycrystalline diamond as a coating on the surface of the implant is also an efficient method to improve the biocompatibility of the implant. Rifai et al [150] first applied chemical vapor deposition to apply the crystal diamond coating into the titanium alloy, which enriched the Ti-6Al-4V SLM biomedical implants application.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Cleaned components are further sterilized with autoclave, gamma irradiation, oxygen plasma, or ultraviolet light. Recently, it was discovered that polycrystalline diamond (PCD) can be applied to coat implants with multiple benefits [33]. PCD coating could be applied for completely sealing off residual abrasives on waterjet-machined implants.…”
Section: Out-of-plane Curved Featuresmentioning
confidence: 99%